2014
DOI: 10.3390/su6020702
|View full text |Cite
|
Sign up to set email alerts
|

Energy Consumption and Energy Efficiency of the Transportation Sector in Shanghai

Abstract: This article investigates changes in the transportation sector in Shanghai between 2000 and 2010 and the implications of this on transportation energy consumption and energy efficiency. The results show that from 2000 to 2010: (1) the traffic energy consumption increased from 597.96 million tons of carbon to 2070.22 million tons of carbon, with an average annual growth rate of 13.49%, and oil met 94.49% of this energy demand by 2010; (2) among present transportation modes, waterway transportation accounts for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…In recent years, the increase in energy consumption is recorded in the industrial [ 1 , 2 ] and global transportation [ 3 , 4 ] sectors, mainly as a result of increased economic activity and mobility of people across the country. Among the various types of energy, fossil energy shows the greatest number of energy consumption to supply global electricity in the industrial and global transportation [ 3 , 5 ]. The massive exploitation of fossil energy leads to the reduction in a large scale of fossil energy, and it takes a long time to be available again in nature, hundreds to thousands of years.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the increase in energy consumption is recorded in the industrial [ 1 , 2 ] and global transportation [ 3 , 4 ] sectors, mainly as a result of increased economic activity and mobility of people across the country. Among the various types of energy, fossil energy shows the greatest number of energy consumption to supply global electricity in the industrial and global transportation [ 3 , 5 ]. The massive exploitation of fossil energy leads to the reduction in a large scale of fossil energy, and it takes a long time to be available again in nature, hundreds to thousands of years.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the largest oil consumption for Shanghai was transport sector. Due to the rapidly increasing trend in passenger traffic and rotation volume, freight transport and cargo rotation volume from 2000 to 2011, the energy used in transport, especially petroleum products consumption, has continued to grow at a significant rate (Song et al, 2014). The other finding shown in the consumption structure table is that industry use accounts for a certain proportion for all regions rather than the agriculture use.…”
Section: Natural Gasmentioning
confidence: 67%
“…However, after considering the heterogeneity of transportation structure, it is found that, under the same conditions, the increased carbon emissions of freight transportation are significantly higher than the increase of passenger transportation [5]. Also, the carbon emission efficiency of railway transportation is better than that of private use of cars [6]. With the diversification of transportation means and the convenience of transportation infrastructure, the introduction of environmental protection policies and the use of low-carbon transportation are increasingly important to reduce carbon emissions [7][8][9].…”
Section: Introductionmentioning
confidence: 99%